2021
DOI: 10.1539/eohp.2021-0006-oa
|View full text |Cite
|
Sign up to set email alerts
|

Increased COVID-19-related workplace bullying during its outbreak: a 2-month prospective cohort study of full-time employees in Japan

Abstract: Objectives: This 2-month cohort study aimed to investigate the changing prevalence and factors associated with COVID-19-related workplace bullying among the general workers in Japan. Methods: A baseline survey was conducted of 4,120 full-time workers at Time 1 (March 2020) and they were invited to a follow-up survey at Time 2 (May 2020) after the outbreak of COVID-19 in Japan. The prevalence of COVID-19-related workplace bullying was compared between Time 1 and Time 2 by using McNemar's test. Multiple logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…HCWs had a significantly higher prevalence of COVID-19- related WBH than non-HCWs at T2 (May 2020), as we already reported earlier 13 . The present study additionally found that the prevalence of COVID-19-related WBH was non-significantly but consistently greater among HCWs than non-HCWs at T3 (August 2020) and T4 (November 2020).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…HCWs had a significantly higher prevalence of COVID-19- related WBH than non-HCWs at T2 (May 2020), as we already reported earlier 13 . The present study additionally found that the prevalence of COVID-19-related WBH was non-significantly but consistently greater among HCWs than non-HCWs at T3 (August 2020) and T4 (November 2020).…”
Section: Discussionsupporting
confidence: 83%
“…The distinction of the settings (community or workplace) and types of perpetrators (from someone within the workplaces, such as supervisors/colleagues, or someone from outside of the organization, such as customers or patients) is important because the legal and ethical frameworks for developing countermeasures to prevent WBH are different depending on these characteristics of WBH 12 . We previously reported that the prevalence of COVID-19-related WBH among HCWs was 6.3% and 9.9%, respectively, as measured early (March 2020) and in the middle (May 2020) of the first outbreak of COVID-19 in Japan, and that the prevalence for HCWs was greater than for non-HCWs 13 . Another previous study reported the prevalence of COVID-19-related customer harassment experienced by HCWs was 10.8% 14 .…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Otra variable es la violencia laboral, ésta puede presentarse como bullying o intimidación, donde los empleados son agredidos constantemente de manera psicológica o física, haciendo que se sientan constantemente atacados y con estrés (Tracy et al, 2006). El modelo de teletrabajo traído por el COVID-19 ha agravado la situación del acoso cibernético en empleados (Iida et al, 2021). Respecto a la interferencia trabajo-familia, la literatura contempla múltiples situaciones en las que los modelos de trabajo causan conflicto con la vida personal (Piotrowski et al, 2020).…”
Section: Introductionunclassified